2009
DOI: 10.1128/jb.01455-08
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Gene Regulation by the agr System in Clostridium perfringens

Abstract: A gram-positive anaerobic pathogen, Clostridium perfringens, causes clostridial myonecrosis or gas gangrene in humans by producing numerous extracellular toxins and enzymes that act in concert to degrade host tissue. The agr system is known to be important for the regulation of virulence genes in a quorum-sensing manner in Staphylococcus aureus. A homologue for S. aureus agrBD (agrBD Sa ) was identified in the C. perfringens strain 13 genome, and the role of C. perfringens agrBD (agrBD Cp ) was examined. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
160
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(168 citation statements)
references
References 29 publications
5
160
0
1
Order By: Relevance
“…perfringens carries a chromosomal operon with partial homology to the S. aureus operon encoding components of the Agr quorum-sensing (QS) system. This agr-like operon was shown to regulate CPA and PFO production by C. perfringens type A strain 13, presumably by encoding components of a similar QS system (155,156). It also controls the production of several plasmid-encoded C. perfringens toxins, including CPB2 and CPE expression in type A strain F5603 (157), CPB production in type C strain CN3685 (158) and type B strains CN1793 and CN1795 (159), and ETX production in type D strain CN3718 (154).…”
Section: The Agr-like Regulatory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…perfringens carries a chromosomal operon with partial homology to the S. aureus operon encoding components of the Agr quorum-sensing (QS) system. This agr-like operon was shown to regulate CPA and PFO production by C. perfringens type A strain 13, presumably by encoding components of a similar QS system (155,156). It also controls the production of several plasmid-encoded C. perfringens toxins, including CPB2 and CPE expression in type A strain F5603 (157), CPB production in type C strain CN3685 (158) and type B strains CN1793 and CN1795 (159), and ETX production in type D strain CN3718 (154).…”
Section: The Agr-like Regulatory Systemmentioning
confidence: 99%
“…Since the highly conserved agr-like operon present among most or all C. perfringens strains apparently does not encode the AgrA/ AgrC two-component system of the S. aureus Agr QS operon (155,156), it was proposed that C. perfringens uses the VirS/VirR system for responding to Agr-like regulatory system signaling (155). While this putative relationship may yet explain the regulation of some toxins by some C. perfringens strains, recent results indicated that Agr-like regulatory system signaling in this bacterium does not always require the VirS/VirR system (154).…”
Section: The Agr-like Regulatory Systemmentioning
confidence: 99%
“…The accessory growth regulator (Agr)-like quorum sensing (QS) system was first discovered in Staphylococcus aureus, where it controls gene expression via population density-induced autoinducer signaling molecules (8,12,13). Within the past 5 years, an Agr-like QS system has also been identified in C. perfringens, where this QS system was first demonstrated to regulate the production of CPA and PFO by type A strain 13 (12, 13).…”
mentioning
confidence: 99%
“…In some cases, regulatory RNAs are involved in VirS/VirR-mediated regulation, although production of perfringolysin O (PFO) is directly regulated by the binding of phosphorylated VirR to DNA sequences, named VirR boxes, that are located directly upstream of the pfoA gene (6, 9). In contrast, the production of the enterotoxin (CPE) during sporulation is mediated by sporulation-specific alternative sigma factors (4, 10, 11).The accessory growth regulator (Agr)-like quorum sensing (QS) system was first discovered in Staphylococcus aureus, where it controls gene expression via population density-induced autoinducer signaling molecules (8,12,13). Within the past 5 years, an Agr-like QS system has also been identified in C. perfringens, where this QS system was first demonstrated to regulate the production of CPA and PFO by type A strain 13 (12, 13).…”
mentioning
confidence: 99%
“…While the LuxS quorum sensing system does not seem to be important for host cell-induced upregulation of toxin production, two studies recently showed that inactivating the agrB gene in C. perfringens type A strain 13 delays the onset of α-toxin and PFO production when this strain grows in bacterial media. 17,18 Those findings open the possibility that the Agr quorum sensing system might also be involved in host-cell induced toxin upregulation by type C isolates.…”
Section: Questions For Future Researchmentioning
confidence: 95%